“To enter oneself”: the spatialization of the subject in Julia de Burgos’ poetry (Anclajes, 2017)
A great number of spatial metaphors shape feminine subjectivity in the poetic works of Julia de Burgos (Carolina, Puerto Rico, 1914–Nueva York, 1953). Appealing to the hypothesis by Michel Collot (2005) which interprets the “spatialization of the subject” as a characteristic note of the modern lyrical pact, we intend to examine how, through this strategy, Julia de Burgosʼpoetry endorses diving in her interiority as a privileged way to create her own poetic world. In this sense, we hope to demonstrate that Burgosʼ writing integrates concerns inherited from Modernism and echoes the resignifications carried out by Spanish American women poets in the first decades of the twentieth century, in regard to the struggle to express a distinctive, autonomous and critical poetic voice.
Keywords: Julia de Burgos; Women’s Poetry; Latin American Literature; Modern Poetry; Space